THE NATURE AND FEATURES OF JUDICIAL ACTS OF THE ADMINISTRATIVE COURT IN CASES OF CHALLENGING THE LEGALITY OF NORMATIVE LEGAL ACTS - Dilbandyan, Oksana (State and Law, 2021)
The article is devoted to the nature and features of judicial acts of the Administrative Court of RA in cases of challenging the lawfulness of normative legal acts. As a result of the research the lawmaking nature of the judicial acts of the administrative court on cases challenging the normative legal acts, as well as the normative nature of the judicial act on invalidating the normative legal act is revealed. Furthermore, several issues related to the peculiarities of judicial acts in cases of challenging the lawfulness of normative legal acts are considered and respective conclusions are made.
Keywords: challenging the lawfulness of normative legal acts; judicial acts of administrative court on challenging the lawfulness of normative legal acts; judicial act on invalidating the normative legal act; administrative proceedings